Chronic cavitatory aspergilloma in an old emaciated patient with review of three cases - Kamble, Mayuri A.; Thawait, Anand P.; Kamble, Ashok T. (International Surgery Journal, 2016)
Aspergilloma is aspergillus fungus overgrowth, most frequently in upper respiratory passages or lung, in a spatial configuration. Chronic cavitatory or cystic parenchymal disease, causing damage to bronchial tree, predisposes to aspergilloma. It produces significant morbidity and requires early surgical intervention. The controversies still exists regarding medical and surgical management of aspergilloma. With decreasing incidence of tuberculosis, surgery is now less challenging for aspergilloma, with improved outcome, during past three decades. Presenting here is a case of giant aspergilloma involving the left upper and middle lobe, which had been progressively increasing since 15 years, in a patient with no history of tuberculosis, with two more cases, along with symptoms and signs, operative and perioperative management, as well as literature review of this rare, clinically important entity.